Droplet digital PCR‐aided screening and characterization of Pichia pastoris multiple gene copy strains. Issue 7 (16th March 2016) - Cámara, Elena; Albiol, Joan; Ferrer, Pau
ABSTRACT: Pichia (syn. Komagataella ) pastoris is a widely used yeast platform for heterologous protein production. Expression cassettes are usually stably integrated into the genome of this host via homologous recombination. Although increasing gene dosage is a powerful strategy to improve recombinant protein production, an excess in the number of gene copies often leads to decreased product yields and increased metabolic burden, particularly for secreted proteins. We have constructed a series of strains harboring different copy numbers of a Rhizopus oryzae lipase gene ( ROL ), aiming to find the optimum gene dosage for secreted Rol production. In order to accurately determine ROL gene dosage, we implemented a novel protocol based on droplet digital PCR (ddPCR), and cross validated it with conventional real‐time PCR. Gene copy number determination based on ddPCR allowed for an accurate ranking of transformants according to their ROL gene dosage. Results indicated that ddPCR was particularly superior at lower gene dosages (one to five copies) over quantitative real‐time PCR (qPCR). This facilitated the determination of the optimal ROL gene dosage as low as two copies. The ranking of ROL gene dosage versus Rol yield was consistent at both small scale and bioreactor chemostat cultures, thereby easing clone characterization in terms of gene dosage dependent physiological effects, which could be discriminated even among strains differing by only one ROL copy. A selected two‐copy strain showed twofold increase in Rol specific production in a chemostat culture over the single copy strain. Conversely, strains harboring more than two copies of the ROL gene showed decreased product and biomass yields, as well as altered substrate consumption specific rates, compared to the reference (one‐copy) strain. Biotechnol. Bioeng. 2016;113: 1542–1551. © 2015 Wiley Periodicals, Inc. Abstract : Comparison between quantitative real‐time PCR (qPCR) and droplet digital PCR (ddPCR) workflow for gene dosage quantification in Pichia pastoris . With qPCR, a standard curve is necessary for the gene of interest (GOI) and the reference (house‐keeping) gene, and several methods are available to calculate the gene copy number. DdPCR is based on the partition of the sample in thousands of droplets, and the detection of the specific signal of the GOI and the reference gene. Ct, cycle threshold; STD, standard curves.